If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -2(3) = x Multiply -2 * 3 3 + -6 = x Combine like terms: 3 + -6 = -3 -3 = x Solving -3 = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -3 + -1x = x + -1x Combine like terms: x + -1x = 0 -3 + -1x = 0 Add '3' to each side of the equation. -3 + 3 + -1x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -1x = 0 + 3 -1x = 0 + 3 Combine like terms: 0 + 3 = 3 -1x = 3 Divide each side by '-1'. x = -3 Simplifying x = -3
| (2x-8)-(x-4)=2 | | 12+-9= | | x^2+y^2+24x-6y+144=0 | | -3y=3x-2 | | 6(11/26)+2y=9 | | 272=34p | | (x-6)-(2x-8)=1 | | P=3+7t | | 10x+4=-3x-17+5x-4 | | x-2(3)=8 | | 5=-3x-3y | | x-8y=-1 | | 3.2=8.73+x | | 10y-5=27y-90 | | 8x-3(2x+3)=-3 | | x-9y=-2 | | -10=5(w-4) | | 5+7=7+5 | | 10v=-16v+182 | | 12(x+5)=16(x+3) | | 9(l+2)=3(l-3) | | 2x+3(10-x)=25 | | 8+2x=7x-2 | | 15x+73=-347 | | 2(4x-5)-3(-x+6)=2/5(15x-65) | | 8x-12+4=8x-8 | | -5+7x=-4x+39 | | 3x+15+5x=-1 | | 3d^2+7d-6=0 | | 2y=3y-15 | | -3n(4b)+2a(3b)= | | 10x-9=2x-69 |